2008
DOI: 10.1007/s00381-008-0653-1
|View full text |Cite
|
Sign up to set email alerts
|

Babies with myelomeningocele in Poland: parents’ attitudes on fetal surgery versus termination of pregnancy

Abstract: On the basis of these results, it was concluded that this population is potentially interested in the use of fetal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Mothers who visit a physician regularly during pregnancy can be diagnosed earlier, and they may have the opportunity to terminate the pregnancy in the early period. However, families rarely terminate a pregnancy due to the socio-cultural characteristics of our country [24]. Although nearly three quarters of the neonates had been diagnosed with meningomyelocele during the antenatal period in our study, none of the families terminated the pregnancy.…”
Section: Discussionmentioning
confidence: 74%
“…Mothers who visit a physician regularly during pregnancy can be diagnosed earlier, and they may have the opportunity to terminate the pregnancy in the early period. However, families rarely terminate a pregnancy due to the socio-cultural characteristics of our country [24]. Although nearly three quarters of the neonates had been diagnosed with meningomyelocele during the antenatal period in our study, none of the families terminated the pregnancy.…”
Section: Discussionmentioning
confidence: 74%
“…A diagnosis of MMC was made antenatally in 60% of our patients. Unfortunately, due to socio-cultural taboos regarding abortion, none of the families had consented to medical termination of pregnancy7).…”
Section: Discussionmentioning
confidence: 99%
“…However, most families rarely opt for the termination of pregnancy. 12 Although about 27.8% of patients have been diagnosed with meningomyelocele during antenatal period in our study, none of the families have opted for termination of pregnancy. In many studies, it has been found that meningomyelocoele is most commonly located in the lumbar region.…”
Section: Discussionmentioning
confidence: 64%
“…Additional anomalies which are found are hydrocephalus and Chiari II malformation. 12 In children with MMC, increased intracranial pressure and hydrocephalus occur within the first month of life. Hydrocephalus was the most common anomaly encountered in our study (50%).…”
Section: Discussionmentioning
confidence: 99%